Pengaruh Firm Size, Company Growth, Leverage, dan Net Working Capital Terhadap Cash Holding pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia - Uut Rahmawati; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of Firm Size, Company Growth, Leverage, and Net Working Capital on Cash Holding in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This study uses a quantitative approach with secondary data obtained from the annual financial reports of companies listed on the Indonesia Stock Exchange. The sample was selected using a purposive sampling method. The data were analyzed using multiple linear regression with the Prais-Winsten AR(1) method to address autocorrelation in the research model. The results indicate that Firm Size, Company Growth, and Leverage do not have a significant effect on Cash Holding. Meanwhile, Net Working Capital has a negative and significant effect on Cash Holding. These findings indicate that companies with higher Net Working Capital tend to hold lower levels of cash because current assets other than cash can serve as alternative sources of liquidity to meet short-term operational and financial obligations. Simultaneously, Firm Size, Company Growth, Leverage, and Net Working Capital have a significant effect on Cash Holding. The findings of this study indicate that Cash Holding policies are influenced by a combination of the company's financial characteristics and liquidity conditions, with Net Working Capital being an important factor in determining the level of cash held by the company.